Clinical significance of enlarged cardiophrenic lymph nodes by CT in advanced ovarian cancer - Song, Sisi; Chen, Huizhu; Ning, Gang; Guo, Yingkun; Li, Xuesheng (Frontiers in Oncology, 2023)
Aim This study aims to assess the clinical influence of enlarged cardiophrenic lymph nodes (CPLN) on staging computed tomography (CT) among patients with advanced ovarian cancer. Methods This retrospective cohort study included 320 patients with advanced epithelial ovarian cancer who underwent staging CT from 2008 to 2019. The CPLN diameter was the average of two radiologists' measurements. Enlarged CPLN was defined as a short-axis diameter of ≥5 mm. Clinical and imaging findings, management decisions, and progression-free survival(PFS) were compared between patients with and without enlarged CPLN. Results Enlarged CPLN was found in 129 (40.3%) patients, which was significantly associated with more pelvic peritoneal carcinomatosis (odds ratio [OR]: 6.61 with 95% confidence interval [CI]: 1.51–28.99), and involved the greater omentum (OR: 6.41, 95% CI: 3.05–13.46), spleen capsule nodules (OR: 2.83, 95% CI: 1.58–5.06), and liver capsule nodules (OR: 2.55, 95% CI: 1.57–4.17). The optimal cytoreduction rates did not differ between patients with and without enlarged CPLN (p = 0.656). The presence of enlarged CPLN had a significant negative influence on PFS (median PFS, 23.5 vs. 80.6 months, respectively, CPLN ≥5 mm versus <5 mm; p = 0.023) in patients with no RD after primary debulking surgery, but no adverse effect on PFS among patients with RD (median PFS, 28.0 vs. 24.4 months, respectively, CPLN ≥5 mm versus <5 mm; p = 0.359). However, enlarged CPLN on staging CT did not affect PFS in patients treated with neoadjuvant chemotherapy, with (median PFS, 22.4 vs. 23.6 months, respectively, CPLN ≥5 mm versus <5 mm; p = 0.360) or without RD (median PFS, 17.7 vs. 23.3 months, respectively, CPLN ≥5 mm versus <5 mm; p = 0.400). The enlarged CPLN showed a decreased trend in 81.6% (n = 80) of the patients with enlarged CPLN. No significant difference was found in PFS (p = 0.562) between patients with decreased and increased in the size of CPLN. Conclusions Enlarged CPLN on staging CT is associated with more abdominal disease but is not reliable in predicting complete resection. Enlarged CPLN awareness is necessary for patients with a primary chance of complete resection of abdominal disease.